Website User Interface Modelling to Enhance Sociability for Autism Spectrum Disorder (ASD) Children Using User Centered Design Method - Dwiafian, Muhammad Rezky; Junaedi, Danang; Adrian, Monterico (eProceedings of Engineering, 2023)
Abstract-Autism Spectrum Disorder (ASD) in Children are those who are suffering from problems during their growing phases. Usually, ASD children have a common problem based on Autism Treatment Evaluation Checklists (ATEC) that consist of Cognitive Problems, Communication & Language Problems, Emotional/Behavioural Problems, and Social Problems. Concerning the sides of the social problem trying to figure out the solution in improving their sociability. One of social skill is empathy to others. Furthermore, it turns out that there is one mobile application developed focusing on this issue named “Kloog2”. The pitfall for this application is having issues such as the content of the word is lengthy and too many step require to do some action. Furthermore, with website it is compatible to work both mobile devices, personal computer and those who are running older operating system that is embedded with web browser. To solve it, creating model to improve sociability skill, by creating a model for them to learn the empathy skill via storytelling method with User Centered Design. The prototype was built and was tested using SUS. The score that was obtained was 74 that translated to acceptable.Keywords-autism spectrum disorder, ASD, user centered design, sociability,socialskill